2010
DOI: 10.1007/s00020-010-1763-1
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Dirac Operator From Nodal Data

Abstract: Inverse nodal problems consist in constructing operators from the given nodes (zeros) of their eigenfunctions. In this work, we deal with the inverse nodal problem of reconstructing the Dirac operator on a finite interval. We prove that a dense subset of nodal points uniquely determine the parameters of the boundary conditions, the mass of a particle and the potential function of the Dirac system. We also provide a constructive procedure for the solution of the inverse nodal problem. Mathematics Subject Classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…However, it is outside the scope of this paper, the interested reader may consult [3,12,24] for recent developments. We note that the obtained results are natural generalizations of the well-known results on inverse nodal problems for the Dirac operator which were studied in [27,28].…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…However, it is outside the scope of this paper, the interested reader may consult [3,12,24] for recent developments. We note that the obtained results are natural generalizations of the well-known results on inverse nodal problems for the Dirac operator which were studied in [27,28].…”
Section: Resultsmentioning
confidence: 63%
“…Such problems play an important role in mathematics and have many applications in natural sciences and engineering (see [1,2,15,[20][21][22]29] and the references therein). The inverse nodal problem, first posed and solved by McLaughlin [13,23], is the problem of constructing operators from given nodes (zeros) of their eigenfunctions (refer to [3][4][5]12,14,17,24,[26][27][28]). From the physical point of view this corresponds to finding, e.g., the density of a string or a beam from the zero-amplitude positions of their eigenvibrations.…”
Section: Introductionmentioning
confidence: 99%
“…Inverse nodal problems have been addressed by various researchers in several papers for different operators [4], [5], [6], [7], [8], [9], [10], [11] and [12]. The inverse nodal problems for Dirac operators with various boundary conditions have been studied and shown that the dense subsets of nodal points which are the first components of the eigenfunctions determines the coefficients of discussed operator by Yang C-F, Huang Z-Y [13]; Yang C-F, Pivovarchik VN [14] and Guo Y, Wei Y [15].…”
Section: Introductionmentioning
confidence: 99%
“…Inverse nodal problems for Sturm-Liouville or diffusion operators have been studied in the several papers ( [1], [2], [3], [6], [14], [15], [16], [19] and [20]). The inverse nodal problems for Dirac operators with various boundary conditions have been solved in [8], [18] and [21]. In their works, it was shown that the zeros of the first components of the eigenfunctions determines the coefficients of operator.…”
Section: Introductionmentioning
confidence: 99%